ENTREPRENEURIAL COMPETENCE AND SELF-EFFICACY AS KEY DRIVERS OF WOMEN'S FASHION MSMES SUCCESS WITH GOVERNMENT SUPPORT IN CENTRAL JAKARTA - Lavenia, Lavenia; Ie, Mei (Graduate Program of Universitas Tarumanagara, 2025)
The success of Micro, Small, and Medium Enterprises (MSMEs) is influenced not only by internal factors but also by various external factors that can strengthen or weaken business performance. This study aims to analyze the effect of government support as a moderator of entrepreneurial competence and self-efficacy on business success in women's fashion MSMEs in Central Jakarta. The research employs a purposive sampling technique with 225 respondents, consisting of women’s fashion MSMEs owners in Central Jakarta. Data analysis was conducted using Partial Least Square – Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The research instrument consisted of an online questionnaire distributed to respondents meeting the sample criteria. The result show that entrepreneurial competence, self-efficacy, and government support have a positive and significant effect on the business success of women's fashion MSMEs in Central Jakarta. However, government support was not found to strengthen the effect of entrepreneurial competence and self-efficacy on the business success. Thus, entrepreneurial competence, self-efficacy, and government support are vital for success in fashion MSMEs. MSMEs business owners can enhance their success by developing entrepreneurial competence and self-efficacy, focusing on innovation, strategic decision-making, and self-confidence as key drivers of business success in the fashion industry. With government support, including training, and access to capital, fashion MSMEs can grow, compete in broader markets, and contribute to local economic development.